Quality Control to Incompatibility of Midsole Products with ISO 9001:2008 Analysis - Isna Nugraha; Restu Hikmah Ayu Murti; Tasya Ambar Aimia; Muhammad Abdus Salam Jawwad; Bekti Nugrahadi; Nur Aini Fauziyah; Reva Edra Nugraha (Future Science, 2022)
The midsole is an inseparable component of the shoe. For this reason, midsole production must be fulfilled so that the needs of shoe manufacturers to produce shoes can be met according to the target. Midsole Jepara factory is one of the work units of PT. X is a company that processes Compound raw materials into Midsole as its main product. ISO 9001:2008 is an international standard for quality management systems. ISO 9001:2008 establishes requirements and recommendations for the design and assessment of a quality management system. It is expected that the products produced from an international quality management system, will be of good quality (standard). Based on this, this study will discuss the quality assurance contained in a manufacturing company to prevent the absence of things that cause product defects. In analyzing the implementation of ISO 9001:2008 used is the analysis of P control maps, fishbone diagrams, and Pareto diagrams. In controlling the midsole products it produces, PT X applies a policy regarding product quality standards, namely using the PDCA (Plan Do Check Action) quality standard.